PERLINDUNGAN HUKUM BAGI KONSUMEN TERKAIT PEREDARAN PANGAN HASIL REKAYASA GENETIKA DI INDONESIA - Yuliati Yuliati (Arena Hukum, 2018)
AbstractThe distribution of food products containing genetic modified organism (GMO) in the market has the potential ito harm the public as consumers, even though consumers have the right to food security and the right to obtain information protected by Act Number 8 year 1999 on Consumer Protection. This article is a legal research that use statutes approach. The result shows that the government of Indonesia has provide adequate legal protection for consumers regarding the distribution of food product containing GMO in the form of the obligation to conduct safety testing of engineering products for business actors as outlined in Government Regulation No.21 Year 2005. Meanwhile, the government has also provided a clear definition of prohibited activities as well as sanction as stated on Consumers Protection Act and Food Act.Â AbstrakBeredarnya produk pangan hasil rekayasa genetika di pasaran, berpotensi merugikan masyarakat sebagai konsumen produk tersebut, padahal konsumen memiliki hak atas keamanan pangan dan hak untuk mendapat informasi yang dilindungi oleh Undang-Undang Perlindungan Konsumen. Artikel ini adalah hasil penelitian hukum yuridis normatif dengan pendekatan perundang-undangan. Hasil penelitian menunjukkan bahwa pemerintah Indonesia telah memberikan perlindungan hukum yang memadai bagi konsumen atas peredaran produk pangan rekayasa genetika baik sebelum peredaran produk dalam bentuk keharusan untuk melakukan uji keamanan produk rekayasa Â bagi pelaku usaha yang dituangkan dalam Peraturan Pemerintah No.21 Tahun 2005 tentang keamanan hayati produk rekayasa genetika dan kewajiban bagi pelaku usaha untuk memenuhi kewajiban tentang pelabelan produk pangan yang mengandung rekayasa genetika.